2005
DOI: 10.17221/4179-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of selected toxic elements (cadmium, lead, mercury and arsenic) in ewe milk in dependence on lactation stage

Abstract: ABSTRACT:Biological investigations on ewes of Merinolandschaf breed (n = 10) were conducted by the 60 th lactation day during the summer on pasture. Ewe milk sampling was carried out on the 2 nd ; 10 th ; 30 th and 60 th lactationday. An electrothermal technique was used to determine Cd and Pb concentrations in food and milk whereas As and Hg concentrations in food and milk were determined by a hydrid technique on an atomic absorption spectrophotometer. The investigation results indicate that concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
(18 reference statements)
2
7
0
Order By: Relevance
“…In case of Pb (Arora et al, 2014;Farell et al, 2013;Shepherd et al, 2012), barium (Ba; Austin et al, 2013), calcein and oxytetracycline (Kierdorf et al, 2013), it has been shown that dentine can give a spatially-resolved record of exposure to these elements/compounds during tooth formation, whereby the concentration of the compound or element in question in the dentine reflects the degree of exposure to the compound or element while this section of the dentine was formed/mineralised. Consistent with this, the change from the Pb-rich mixed milk/grass diet of lambs to the Pb-poor seaweed diet of adult North Ronaldsay sheep (Anastasio et al, 2006;Antunovic et al, 2005;Bacon et al, 1996;Hansen et al, 2003a;Najarnezhad et al, 2015;Ródenas de la Rocha et al, 2009;Schiener et al, 2015) is visible in the bioimages of our study: The arrows in Fig. 2E point out changes in Pb intensities in the primary dentine, with arrows originating in the younger primary dentine where lower intensities were observed and pointing toward the higher intensities in older primary dentine.…”
Section: Origin Of Arsenic In Seaweed-eating Sheep's Teethsupporting
confidence: 88%
See 1 more Smart Citation
“…In case of Pb (Arora et al, 2014;Farell et al, 2013;Shepherd et al, 2012), barium (Ba; Austin et al, 2013), calcein and oxytetracycline (Kierdorf et al, 2013), it has been shown that dentine can give a spatially-resolved record of exposure to these elements/compounds during tooth formation, whereby the concentration of the compound or element in question in the dentine reflects the degree of exposure to the compound or element while this section of the dentine was formed/mineralised. Consistent with this, the change from the Pb-rich mixed milk/grass diet of lambs to the Pb-poor seaweed diet of adult North Ronaldsay sheep (Anastasio et al, 2006;Antunovic et al, 2005;Bacon et al, 1996;Hansen et al, 2003a;Najarnezhad et al, 2015;Ródenas de la Rocha et al, 2009;Schiener et al, 2015) is visible in the bioimages of our study: The arrows in Fig. 2E point out changes in Pb intensities in the primary dentine, with arrows originating in the younger primary dentine where lower intensities were observed and pointing toward the higher intensities in older primary dentine.…”
Section: Origin Of Arsenic In Seaweed-eating Sheep's Teethsupporting
confidence: 88%
“…After four to six months, when the lambs are weaned, ewes and lambs are brought back onto the beaches (Hillson, 2005;Upex and Dobney, 2012) where they subsist nearly exclusively on seaweed (Hansen et al, 2003a). The North Ronaldsay seaweed diet has been shown to contain three to four orders of magnitude more As than in the milk/grass diets when considering dietary uptake per kg of sheep body weight (Antunovic et al, 2005;Hansen et al, 2003aHansen et al, , 2003b. The second set of teeth (third molars, n = 5) originates from a modern population of Shetland sheep grazing on grass and maritime heath in the parish of South Walls on the island of Hoy (part of Orkney archipelago).…”
Section: Sample Descriptionsmentioning
confidence: 99%
“…Kędzierska-Matysek et al (2015) found that the content of Mn in goat milk was lowest in colostrum, which was similar to our study. The changes in the contents of As were similar (Antunović et al, 2005). For buffalo, we found that the contents of Cu, Co, and Se declined as lactation increased.…”
Section: Discussionsupporting
confidence: 71%
“…The atomic absorption spectrometry (AAS) technique is widely employed to determine the quantitative and qualitative elements in a sample (19). This technique is considered the best to measure the concentrations of trace elements with the detection limit less than part per billion (ppb) (20).…”
Section: Atomic Absorption Spectrometry (Aas)mentioning
confidence: 99%